2005
DOI: 10.1080/09687630410001712681
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent marijuana use intentions: using theory to plan an intervention

Abstract: This paper uses an integrated model of behavior change to predict intentions to use marijuana occasionally and regularly in a US-based national sample of male and female 12 to 18 year olds (n ¼ 600). The model combines key constructs from the theory of reasoned action and social cognitive theory. The survey was conducted on laptop computers, and half of the sample was female. The analysis serves as a basis for discussion about using theory in various stages of planning a campaign to decrease marijuana use amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, subsequent studies using theories such as the theory of normative social behavior (Rimal & Real, 2003; 2005) found evidence suggesting that descriptive norms exert significant influence over behavior (Lapinski, Rimal, DeVries, & Lee, 2007; Rimal, 2008). Furthermore, measures which combine both types of norms have been found to explain additional variance in behavioral intention previously not accounted for by a measure of subjective norms alone (e.g., Albarracin, Fishbein, & Middlestadt, 1998; Rhodes & Courneya, 2003; Sayeed, Fishbein, Hornik, Cappella, & Ahern, 2005). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent studies using theories such as the theory of normative social behavior (Rimal & Real, 2003; 2005) found evidence suggesting that descriptive norms exert significant influence over behavior (Lapinski, Rimal, DeVries, & Lee, 2007; Rimal, 2008). Furthermore, measures which combine both types of norms have been found to explain additional variance in behavioral intention previously not accounted for by a measure of subjective norms alone (e.g., Albarracin, Fishbein, & Middlestadt, 1998; Rhodes & Courneya, 2003; Sayeed, Fishbein, Hornik, Cappella, & Ahern, 2005). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Health communication research (e.g., Heckman, Manne, Kloss et al, 2011) and campaigns (e.g., Sayeed et al, 2005) applying the reasoned-action approach often focus on identifying main effects of behavioral determinants underlying behavior. However, previous studies have shown that interactions between behavioral determinants are possible, and may exert joint effects on behavioral intention.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is consistent with previous studies that have anecdotally observed the same differences. 1,[4][5][6] However, this study also adds to the current literature by statistically showing that the expectancy-based model outperformed the value-expectancy based model in most cases using Steiger's test for comparing two dependent correlations with one variable in common. This supports Fishbein and Ajzen's notion that measuring motivation to comply likely adds error in measuring referent normative pressure, and in determining what referents are important for forming generalized injunctive normative pressure.…”
Section: Discussionmentioning
confidence: 85%
“…This has been demonstrated in a limited number of studies, namely, when evaluating women's intentions to receive a mammogram 3 , seat belt use among college students 4 , and marijuana use among adolescents. 5 This evidence has led Fishbein and Ajzen 1 to note that despite the intuitive appeal of having a value-expectancy measurement model, motivation to comply appears to add little to no value towards predicting injunctive norms. Furthermore, they note that motivation to comply may even add error variance towards predicting injunctive norms, thus creating problems for researchers and practitioners.…”
mentioning
confidence: 99%
“…Theoretically-based research concerning the determinants of drug risk behavior for high risk populations has been conducted from the perspective of the Health Belief Model (Ellickson, McCaffrey, Ghosh-Dastidar, & Longshore, 2003), the Theory of Reasoned Action (Sayeed, Fishbein, Hornik, Capella & Ahern, 2005), and Social-Cognitive Theory (Barkin, Smith, & Durant, 2002). Although this research has contributed to the understanding of substance use and abuse among high risk populations, these models have often focused on a relatively limited array of explanatory constructs and have produced contradictory theoretical perspectives (Noar & Zimmerman, 2005) Moreover, the vast majority of literature related to health behavior theory focuses on using the aforementioned theories to inform interventions rather than explicitly testing, building, or extending the theory under study (Painter, Borba, Hynes, Mays, & Glanz, 2008).…”
mentioning
confidence: 99%